The Balance between Energy, Environmental Security, and Technical Performance: The Regulatory Challenge of Nanofluids - Maria José Lourenço; João Alexandre; Charlotte Huisman; Xavier Paredes; Carlos Nieto de Castro (Nanomaterials, 2021)
Nowadays, numerous studies on nanomaterials (NMs) and Nanofluids (NFs) are account a plethora of applications. With the scientific society’s common goal of fulfilling the target of sustainable development proposed by the UN by 2030, it is necessary to combine efforts based on the scientific and technological knowledge already acquired, to apply these new systems with safety. There are thousands of publications that examine the use of NFs, their benefits and drawbacks, properties, behaviors, etc., but very little is known about the safety of some of these systems at a laboratory and industrial scale. What is the correct form of manipulating, storing, or even destroying them? What is their life cycle, and are they likely to be reused? Depending on the nanoparticles, the characteristics of the base fluid (water, propylene glycol, or even an ionic liquid) and the addition or not of additives/surfactants, the safety issue becomes complex. In this study, general data regarding the safety of NF (synthetic and natural) are discussed, for a necessary reflection leading to the elaboration of a methodology looking at the near future, intended to be sustainable at the level of existing resources, health, and environmental protection, paving the way for safer industrial and medical applications. A discussion on the efficient use of nanofluids with melanin (natural NM) and TiO2 in a pilot heat collector for domestic solar energy applications illustrates this methodology, showing that technical advantages can be restricted by their environment and safety/security implications.